Influencing public policy in Tanzania: Trials and tribulations of the Tanzania Horticultural Association - Irwin, David (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2018)
Interest groups aim to influence public policy and, therefore, interest groups representing business advocate improvements to the business enabling environment. Researchers claim that it is difficult to assess the extent to which interest groups influence public policy. Most research in this area focuses on the US and EU and little explores the factors that may determine whether business membership organisations (BMOs) are likely to be successful. This paper addresses those gaps. It explores the attempts by a BMO in Tanzania, the Tanzania Horticultural Association, to influence reform of public policy. It offers evidence that the association was successful, though mostly on issues that might be regarded as technical rather than contentious or political. The paper reviews the factors that have contributed to its success, which include providing good evidence, preparing a persuasive argument, using champions amongst public officials and engaging in dialogue, without confrontation, across government and concludes that this approach makes a difference in whether BMOs are successful.